Utilização de sementes de Moringa oleifera Lam. no tratamento de água para consumo humano - SALES, Ariele da Silva (2019)
The use of Moringa oleifera Lam. seeds appears as a low cost and sustainable alternative for the treatment of water, considering that there are already researches that prove its potential. The objective of this work was to verify the effect of different concentrations of the Moringa oleifera Lam. seed powder applied in water samples from the Xingu River. The experimental trial had 6 treatments with different concentrations of the powder added to the water samples, besides the control: T0 (water, without addition of powder); T1 (water with 80 mg.L-1 of powder); T2 (water with 120 mg.L-1 of powder); T3 (water with 250 mg.L-1 of the powder); T4 (water with 500 mg.L-1 of the powder); T5 (water with 1000 mg.L-1 of powder) and T6 (water with 2000 mg.L-1 of powder). The solutions, with the appropriate concentrations, were maintained in an environment with controlled temperature of 25 ° C for 24 hours. The analyzed parameters were: Free Chlorine; Apparent Color; Total Iron; pH; Turbidity; Total Escherichia coli and Coliform. The use of Moringa oleifera Lam. seed powder was efficient in relation to the parameters Residual Chlorine Free, Total Iron and Turbidity, showing great potential in its use for water treatment. The use of the Moringa oleifera Lam. seed powder significantly altered the parameters described above, as well as not interfering with the pH value. However, in order to obtain a water suitable for human consumption, it is necessary to combine the treatment with other techniques, in order to obtain the appropriate values required by community. Therefore, it is recommended to carry out more research using the seeds of Moringa oleifera Lam. in the treatment of water, due to the numerous advantages of using this method in both social and environmental issues.